A multilayer assembly of two mixed-valence Mn16-containing polyanions and study of their electrocatalytic activities towards water oxidation. Issue 21 (16th May 2018) - Du, Yu; Yu, Tian; Fu, Zhijing; Bi, Lihua
Abstract : Electrocatalytic activities of two Mn16 cluster-containing polyanions towards water oxidation were comparatively studied in solution and composite films. Abstract : Herein, two mixed-valence Mn16-containing polyanions, (Mn16) [MnIII10MnII6O6 (OH)6 (PO4 )4 (A-a-SiW9 O34 )4 ] 28− (Mn16-Cs) and [MnIII4MnII12(OH)12 (PO4 )4 (A-a-SiW9 O34 )4 ] 28− (Mn16-Rb), were successfully fabricated on an indium tin oxide (ITO)-coated glass electrode and a glass carbon electrode (GCE) by a layer-by-layer assembly method. Moreover, four composite films, i.e. [PDDA/Mn16-Cs] n, [PDDA/Mn16-Rb] n, [Mn16-Cs/Rubpy] n, and [Mn16-Rb/Rubpy] n (PDDA: poly(diallyldimethylammonium chloride); Rubpy: tris(2, 2′-bipyridyl)ruthenium(ii ) chloride; n = 1–10), were constructed for comparison and characterized by UV-visible spectroscopy, cyclic voltammetry (CV), and X-ray photoelectron spectroscopy (XPS). Their electrocatalytic activities towards water oxidation were studied under the same experimental conditions. The results of the controlled experiments indicate that (1) all the four films exhibit expected electrocatalytic activities towards water oxidation; (2) the electrocatalytic activity of Mn16-Cs is better than that of Mn16-Rb in solution and composite films; and (3) the electrocatalytic activities of the composite film [Mn16/Rubpy] n are better than those of the composite film [PDDA/Mn16] n .